Mass budget of the glaciers and ice caps of the Queen Elizabeth Islands, Canada, from 1991 to 2015. (15th February 2017) - Millan, Romain; Mouginot, Jeremie; Rignot, Eric
Abstract: Recent studies indicate that the glaciers and ice caps in Queen Elizabeth Islands (QEI), Canada have experienced an increase in ice mass loss during the last two decades, but the contribution of ice dynamics to this loss is not well known. We present a comprehensive mapping of ice velocity using a suite of satellite data from year 1991 to 2015, combined with ice thickness data from NASA Operation IceBridge, to calculate ice discharge. We find that ice discharge increased significantly after 2011 in Prince of Wales Icefield, maintained or decreased in other sectors, whereas glacier surges have little impact on long-term trends in ice discharge. During 1991–2005, the QEI mass loss averaged 6.3 ± 1.1 Gt yr −1, 52% from ice discharge and the rest from surface mass balance (SMB). During 2005–2014, the mass loss from ice discharge averaged 3.5 ± 0.2 Gt yr −1 (10%) versus 29.6 ± 3.0 Gt yr −1 (90%) from SMB. SMB processes therefore dominate the QEI mass balance, with ice dynamics playing a significant role only in a few basins.